Crispr/Cas Mediated Deletion of PTPN22 in Jurkat T Cells Enhances TCR Signaling and Production of IL-2 - Bray, Cara; Wright, David; Haupt, Sonja; Thomas, Sharyn; Stauss, Hans; Zamoyska, Rose (Frontiers in Immunology, 2018)
A single nucleotide polymorphism, C1858T, in the gene encoding the protein tyrosine phosphatase nonreceptor type 22 (PTPN22) results in one of the strongest genetic traits associated with autoimmune disease outside of the Major Histocompatibility Complex (MHC) genes. However, the consequences of this polymorphism, which introduces an arginine to tryptophan substitution at amino acid 620, for the function of PTPN22 protein is unclear and conflicting results have been obtained in human compared to mouse cells expressing this variant phosphatase. In mouse the variant appears to be a loss-of-function allele resembling a milder form of the null allele, while studies in human cells have reported it to be a gain-of-function mutation. To address whether the phosphatase has distinct functions in mouse versus human T cells, we used CRISPR gene-editing to generate the first example of human PTPN22-KnockOut (KO) T cells. By comparing isogenic human T cells which express or lack PTPN22, we showed that PTPN22 KO T cells displayed enhanced expression of IL-2 and CD69 upon stimulation with cognate antigen. PTPN22 KO cells also showed increased Erk phosphorylation upon stimulation with weak antigen, but the difference was diminished in response to strong antigen, indicating that PTPN22 plays a more critical role in regulating weak-antigen responses. These data are in keeping with a role for PTPN22 in determining the threshold of stimulation required to activate T cells, a critical function of autoimmune pathogenesis. Our data indicate that PTPN22 has comparable functions in mouse and human T cells, and that the conflicting results in the literature regarding the impact of the point mutation are not due to differences in the activity of PTPN22 itself, but may be related to interactions with other proteins or splice variation.